Patient involvement in mental health care: culture, communication and caution. (15th October 2012) - Tse, Samson; Tang, Jessica; Kan, Alice
Abstract Background Patient or service user involvement in mental health services (MHS) is a hallmark of the recovery approach. Objective In this viewpoint article, we review Tambuyzer et al. paper 'Patient involvement in mental health care: One size does not fit all' in order to express our opinion of their work. We also suggest specific actions that may enhance the implementation of patient involvement in MHS. Discussion We make three main points about Tambuyzer et al. model. First, the cultural dimension of patient involvement seems underemphasized in the model. Second, the model might be improved if the increasing role of communications technology in patient involvement is taken into consideration. Third, it is important to acknowledge that the process of patient involvement is not linear, and participation is not a homogeneous experience. Conclusions We suggest that the model be expanded and that further work be carried out on the implementation of patient involvement in MHS.